Sensing Characteristics of ZnO Nanoparticle Film towards Acetone - Chaudhary, Dinesh Kumar; Maharjan, Yogesh Singh; Pradhan Amatya, Sharmila; Shrestha, Shankar Prasad; Parajuli, Rajendra; Shrestha, Pitamber; Pradhan Joshi, Leela (Journal of Institute of Science and Technology, 2022)
Over the past few decades, nanomaterials of metal oxide such as zinc oxide (ZnO) have been significantly researched for sensing various toxic gases like ethanol, acetone and ammonia. The sensing performance of semiconducting materials depends primarily on their surface structure and the interaction behavior with target gas molecules. The surface quality of ZnO is highly influenced by deposition methods. Although several ZnO surfaces have been rigorously studied for detecting gas leakages, it still possesses drawbacks such as high operating temperature, slow response and recovery times. Henceforth, this investigation was carried out to resolve these issues in the fabrication of future ZnO-based gas sensors. In this work, we report the major findings of the ZnO-based nanoparticle film gas sensor prepared by a doctor blade method to gain insight towards detecting various concentrations of acetone gas at different temperatures. The XRD and FTIR results confirmed the phase purity of ZnO. The results showed the highest response ratio of 25.697 0.012 at 285 oC with an exposure of 800 ppm of acetone along with the quick response and recovery times of 39 sec and 79 sec, respectively. This operating temperature was found to be lower than the reported value for a similar system than that prepared via different methods.